2015
DOI: 10.1007/s12119-015-9270-9
|View full text |Cite
|
Sign up to set email alerts
|

Hooking Up as an Individualistic Practice: A Double-Edged Sword for College Women

Abstract: An increasingly large body of literature on the casual sex practice, hooking up, has documented that it tends to yield a wide range of positive and negative outcomes for college women. However, no research exists that provides an integrated explanation of these divergent outcomes. One recent influential attempt to highlight the benefits of hooking up for college women has implied that the individualistic character of the practice facilitates these positive outcomes. By contrast, the research here illuminates h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 36 publications
3
35
0
Order By: Relevance
“…Ambiguity in expectations (i.e., lack of clarity about romantic commitment, closeness, or exclusivity) and lack of communication (Lovejoy, 2015) may contribute to conflicting feelings and emotional vulnerability, such as frustration about unreciprocated deeper feelings and feelings of betrayal (Lovejoy, 2015;Weaver, MacKeigan, & MacDonald, 2011), and consequently to greater psychological distress. Girls may also feel manipulated, even more so if they develop romantic interest, and may blame themselves when their casual partner does not show interest afterward (Meier, 2007;Paul & Hayes, 2002;Lovejoy, 2015). Higher alcohol and drug use may therefore be a strategy to cope with their increased psychological distress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ambiguity in expectations (i.e., lack of clarity about romantic commitment, closeness, or exclusivity) and lack of communication (Lovejoy, 2015) may contribute to conflicting feelings and emotional vulnerability, such as frustration about unreciprocated deeper feelings and feelings of betrayal (Lovejoy, 2015;Weaver, MacKeigan, & MacDonald, 2011), and consequently to greater psychological distress. Girls may also feel manipulated, even more so if they develop romantic interest, and may blame themselves when their casual partner does not show interest afterward (Meier, 2007;Paul & Hayes, 2002;Lovejoy, 2015). Higher alcohol and drug use may therefore be a strategy to cope with their increased psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…The way that a young woman's FWB partner treated her during the relationship may also influence her subsequent psychological well-being (Owen et al, 2013). A qualitative study among college women reported that uneasiness and distress may arise when sex is added to friendship because the new focus on sex may suppress emotional intimacy (Lovejoy, 2015). As Vrangalova (2015a) suggested, when FWB relationships last longer, their effects may also be stronger and longer.…”
Section: Discussionmentioning
confidence: 99%
“…A desire to delay very committed relationships to focus on personal and career development has featured prominently in explanations of the near‐ubiquity of hooking up in college (Bogle ; Hamilton and Armstrong ; Regnerus and Uecker ). Lovejoy summarizes this argument, writing that, “As a sexual practice, it [hooking up] appears to permit privileged college women to pursue the self‐development goals characteristic of contemporary early adulthood, including sexual autonomy and exploration, academic achievement, and career advancement” (:488). In a context where marriage is understood to be years into the future, hookups allow young adults to experiment with sexuality outside of the committed relationships that they do not yet want to develop (Claxton and van Dulmen ).…”
Section: Literaturementioning
confidence: 99%
“…Most research exploring emotional reactions to hookup experiences has focused on factors leading to high levels of regret (Lovejoy, 2015;Grello et al, 2006). Regret is when individuals feels negatively about themselves because of a decision they made or an action they took (Eshbaugh & Gute, 2008).…”
Section: Emotional Reactionsmentioning
confidence: 99%
“…In sum, most research has focused on factors of a hookup that lead to high levels of regret or negative emotional reactions (Grello et al, 2006;Lovejoy, 2015;Owen et al, 2014). The proposed study will examine the factors that lead to lower levels of regret, more positive, and fewer negative emotional reactions following a hookup.…”
Section: Emotional Reactionsmentioning
confidence: 99%